El Excentrico, 1979-08-20 - Garcia, Bert:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2024)
August 20, 1979 [20 de augosto de 1979]. Ano 30, No 9. Cover contains a group photo of Carlos Gomez receiving an award from Bart and Martha Cortez. The headline reads, "La Hora de Mexico: Mr Carlos Gomez honored by Bart and Martha Cortez" (transl: The Time of Mexico).